Coping Strategies of Student Exchange Participants Based on Academic Adjustment Ability - Abiha, Ummu; Mubarok, Ali Syahidin; Putri, Sukma Ari Ragil (FKIP Universitas Lampung, 2024)
Coping Strategies of Student Exchange Participants Based on Academic Adjustment Ability. Objective: This study examines student exchange participants' coping strategies by analysing their academic adjustment ability level. Differences in the level of academic adjustment ability impact the coping strategies they will use. Methods: This study uses a qualitative approach with a case study type. Participants in this study were student exchange participants with low, medium, and high levels of academic adjustment. This criterion was chosen to see the dynamics of coping strategies carried out by student exchange participants. Data collection used interviews using data triangulation as a data credibility test technique. Findings: The results of this study indicate that participants placed more emphasis on problem-focused coping as the focus of the problem to be solved, and all participants managed their emotions to help the coping process. Conclusion: This study shows the importance of psychological assistance for participants to prepare them mentally during the student exchange activity process. Keywords: academic adjustment, coping strategy, student exchange.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024117